Seroconversion to mRNA SARS-CoV-2 Vaccines in Hematologic Patients - Fattizzo, Bruno; Bortolotti, Marta; Rampi, Nicolò; Cavallaro, Francesca; Giannotta, Juri Alessandro; Bucelli, Cristina; Cassin, Ramona; Da Vià, Matteo Claudio; Galassi, Giulia; Noto, Alessandro; Pettine, Loredana; Rossi, Francesca Gaia; et al. (Frontiers in Immunology, 2022)
Hematologic patients show lower responses to SARS-CoV-2 vaccines, but predictors of seroconversion are lacking. In this prospective cohort study, hematologic patients undergoing SARS-CoV-2 mRNA vaccination at a single center in Milan, Italy, were sampled for anti-Spike and anti-Nucleocapside IgG titer at 5+1 weeks and at 3 months from the second vaccine dose. Patients (N=393) received either BNT162b2 (Pfizer-BioNTech, 48%) or MRNA-1273 (Moderna, 52%), and 284 (72%) seroconverted and 100% persisted at 3 months. Non-response was higher in chronic lymphocytic leukemia (CLL) and lymphoma patients, and in those treated with small molecules and monoclonal antibodies. In myeloid neoplasms, lower responses were detected in acute myeloid leukemias treated with venetoclax plus hypomethylating agents and in myelofibrosis receiving ruxolitinib. Multivariable analysis showed that seroconversion was favorably associated with a diagnosis other than indolent lymphoma/CLL [OR 8.5 (95%CI 4.1-17.6)], lack of B-cell depleting therapy [OR 3.15 (1.7-5.9)], and IgG levels within the normal range [OR 2.2 (1.2-4.2)]. We developed a simple algorithm according to these 3 risk factors (A. diagnosis of indolent lymphoma/CLL, B. B-cell depleting treatment and C. low IgG) to predict non-response. IgG levels and treatment may be modifiable risk factors and should be considered for timing of vaccine administration.